Peran Penyuluh Pertanian Dalam Pengembangan Kelompok Tani di Desa Kanaungan Kecamatan Labakkang Kabupaten Pangkep - Musfira Musfira; Azisah Azisah; Abd. Asis Pata (Universitas Muslim Maros, 2024)
This research aims to determine the role of agricultural extension workers in the development of farmer groups in Kanaungan Village, Labakkang District, Pangkep Regency. This research was carried out from March to May 2023. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with members of farmer groups in Kanaungan Village, while secondary data were obtained from documents and reports from the Kanaungan Village office. The method used in processing and analyzing data on farmer group members is qualitative analysis using a Likert scale. The tool used in processing data is Excel 2013 software. The results showed that the role of agricultural extension workers in the development of farmer groups in Kanaungan Village, Labakkang District, Pangkep Regency was included in the high category.